Development of Economic Creativity of Craftsmen Woven Bags from Typical Lombok Rattan Through Digitalization of Business Management in Beleka Village - Hambali Hambali; Maspaini Maspaini; Muhamad Ahyat; Dwi Nurhidayati (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
The Beginner Community Empowerment Program (PMP) aims to increase the knowledge and skills of craftsmen groups, with a focus on the